THE TWO SIDES OF MONEY LAUNDERING - Corina – Maria ENE (Hyperion Economic Journal, 2014)
The mainly goal of money laundering is to carry out more and more illegal economic transactions or activities to produce individual or groups gains and then to legitimate them. Money laundering converts illicit source of money generated by criminal activities in order to hide the connection between money and their original illegal activities. This is one of money laundering side. The second side implies corruption. While money laundering is a passing channel for illicit funds due to its criminal origin source, such funds may derive from corruption offences. All corruption’s forms represent the most important illicit funds branches for money laundering process. Corrupt people methods used to exploit the national and international financial system reflect the relationship between those two criminal activities. Criminals achieve their personal interests by hiding their corruption proceeds and transfer these gains to official economies. Corruption spread in any society entails money laundering spread, and the converse, too. There is a quite “indecent” relationship between money laundering and corruption. This paper tries to identify the multiple connections between the two phenomenons showing the negative impacts these criminal behaviours are having on the national and international economy. We conclude by highlighting the necessity of a multidisciplinary approach in order to fight against money laundering and corruption by integrating these problem frameworks at national level. International community must focus their resources on money laundering and corruption risks areas and maximize their response impact.